Diligent family history to detect a mitochondrial disorder in disguise: Lessons from a case of myoclonic epilepsy - Suvorit S. Bhowmick; Radhay Parikh; Pratishtha Shrivastav (Annals of Movement Disorders)
Mitochondrial disorders often present with ataxia, myoclonus, and epilepsy. Valproic acid may be selected for treating myoclonus if it is the presenting feature. While it is efficacious in suppressing cortical myoclonus, valproic acid is a known mitochondrial toxin and, therefore, not recommended. We report a family carrying the mitochondrial A8344G mutation. The proband, after being treated with valproic acid for myoclonic epilepsy, presented with gradually progressive cerebellar ataxia. He had a re-emergence of myoclonus upon withdrawal of valproic acid about 15 years later. The mitochondrial A8344G mutation, given its diverse clinical manifestations and intrafamilial phenotypic heterogeneity, evaded early recognition. Individuals carrying this mutation need life-long anti-epileptic therapy for myoclonus. Thus, it is important to recognize the mitochondrial disorder and select appropriate drugs.